2007
DOI: 10.1021/ma071106i
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Free-Radical Polymerization of Acrylates and Methacrylates:  Structure−Reactivity Relationship

Abstract: Radical polymerization processes occur through a complex network of many different reactions. It is well-known that the polymerization rate is directly related to the monomer structure. The experimental polymerizability behavior is expressed as k p /k t 1/2 , where k p is the rate coefficient of propagation and k t is the rate coefficient of termination. In this study, the reactivity of a series of acrylates and methacrylates is modeled in order to understand the effect of the pendant group size, the polarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…These results are consistent with ab initio calculations that predict that both, the chain length dependence of k p and its dependence on the size of the ester chain are mainly an effect of the frequency factor, A being affected due to changes in the partition functions of the internal rotations of the propagation polymer chain. [19,[21][22][23][24] The activation energy depends mainly on electronic stabilization of the propagating radical and steric hindrance around the radical centre. E A is therefore expected to vary only by 1-2 kJ Á mol À1 with ester chain length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with ab initio calculations that predict that both, the chain length dependence of k p and its dependence on the size of the ester chain are mainly an effect of the frequency factor, A being affected due to changes in the partition functions of the internal rotations of the propagation polymer chain. [19,[21][22][23][24] The activation energy depends mainly on electronic stabilization of the propagating radical and steric hindrance around the radical centre. E A is therefore expected to vary only by 1-2 kJ Á mol À1 with ester chain length.…”
Section: Resultsmentioning
confidence: 99%
“…Significant discrepancies in the Arrhenius parameters, A and E A , determined by a number of different research groups are found in the past literature, leading to inconsistencies between the conclusions of the individual authors [14][15][16][17][18] and also with theoretical predictions. [19][20][21][22][23][24] To address this problem, Zammit et al performed a comparison of the different calibration techniques in PLP/SEC of a number of poly(alkyl acrylates). These authors stated that -if MHKS parameters were accurately determined preferably using online multi-detection SEC -universal calibration was not the major cause of the observed inter-laboratory discrepancies in k p .…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular hydrogen abstractions like chain transfer to monomer and chain transfer to polymer were studied in various systems [106,[137][138][139][140][141]. Intramolecular hydrogen abstractions were investigated as well, focusing on the backbiting reactions that occur when a chain-end radical (CER) abstracts a hydrogen from its own backbone, forming a mid-chain radical (MCR) [70,106,[141][142][143][144].…”
Section: Secondary Reactionsmentioning
confidence: 99%
“…In several studies it was suggested that the rate of the propagation reaction is largely governed by the relevant rotational modes of the transition state structure. [70][71][72][73][74] In the following text, some experimental aspects are briefly considered. In the main part experimental results are summarized and the origin of the solvent influence on homopolymerization k p is discussed, considering the results from theoretical studies.…”
Section: Introductionmentioning
confidence: 99%